2015
DOI: 10.1093/jhps/hnv075
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive capsulitis of the hip: a review addressing diagnosis, treatment and outcomes

Abstract: Adhesive capsulitis (AC) of the hip (i.e. ‘Frozen Hip’), in part due to its difficulty in diagnosis, is an often overlooked and underappreciated entity of hip morbidity. This review aimed to elucidate a diagnostic approach and the surgical treatment options (with associated outcomes) of employing hip arthroscopy in the setting of AC. Electronic databases (EMBASE, MEDLINE and PubMed) were searched for available sources for all relevant clinical studies addressing the surgical management of AC. Additionally, ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…ACH is a poorly understood condition that can occur without any concomitant pathology [ 2 ].The natural history of the disease starts with inflammatory synovitis and ends with chronic fibrosis [ 3 , 9 ]. Exclusion of other hip pathologies essential, MRA can be used if ACH is suspected; Joo YD et al reported capsular thickening in most of patients with the diagnosis of ACH, especially the superior, and the posterior recess [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ACH is a poorly understood condition that can occur without any concomitant pathology [ 2 ].The natural history of the disease starts with inflammatory synovitis and ends with chronic fibrosis [ 3 , 9 ]. Exclusion of other hip pathologies essential, MRA can be used if ACH is suspected; Joo YD et al reported capsular thickening in most of patients with the diagnosis of ACH, especially the superior, and the posterior recess [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported by Caroit et al [ 1 ]. This condition is commonly affecting young women and may be primary (idiopathic), or secondary to hip surgery, hip infection, or repetitive microtrauma [ [2] , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Failed hip arthroscopy may be defined as persistent postoperative pain and/or stiffness—diagnosed by a combination of decreased joint capacity and global range of motion (ROM)—that does not improve with nonsurgical means [ 5 ]. In a systematic review of 6134 patients, Harris et al [ 6 ] reported a reoperation rate of 6.3% after index hip arthroscopy.…”
Section: Introductionmentioning
confidence: 99%